2006
DOI: 10.1194/jlr.m500401-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Swelling of phospholipids by monovalent salt

Abstract: Critical to biological processes such as membrane fusion and secretion, ion-lipid interactions at the membranewater interface still raise many unanswered questions. Using reconstituted phosphatidylcholine membranes, we confirm here that multilamellar vesicles swell in salt solutions, a direct indication that salt modifies the interactions between neighboring membranes. By varying sample histories, and by comparing with data from ion carrier-containing bilayers, we eliminate the possibility that swelling is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
165
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(189 citation statements)
references
References 51 publications
22
165
1
1
Order By: Relevance
“…Experiments have shown that anionic 4, [22][23][24][25] and cationic 26,27 membranes interact readily with their counterions (especially divalent ones), whereas the interactions of zwitterionic lipid bilayers with salt ions appear rather sensitive to the size and valency of ions. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] As for molecular-level computational studies, the increase in computing power in the past few years has made it possible to extend computer simulations beyond the relatively long relaxation times of tens to hundreds of nanoseconds required for equilibration of ions in lipid/water systems. Although most computational studies by far have focused on the effects of salt ions on zwitterionic (neutral) lipid bilayers, 33,[42][43][44][45][46][47][48][49][50][51][52][53] there is also an increasing number of studies on anionic [54][55][56][57][58][59] and cationic 60,61 lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown that anionic 4, [22][23][24][25] and cationic 26,27 membranes interact readily with their counterions (especially divalent ones), whereas the interactions of zwitterionic lipid bilayers with salt ions appear rather sensitive to the size and valency of ions. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] As for molecular-level computational studies, the increase in computing power in the past few years has made it possible to extend computer simulations beyond the relatively long relaxation times of tens to hundreds of nanoseconds required for equilibration of ions in lipid/water systems. Although most computational studies by far have focused on the effects of salt ions on zwitterionic (neutral) lipid bilayers, 33,[42][43][44][45][46][47][48][49][50][51][52][53] there is also an increasing number of studies on anionic [54][55][56][57][58][59] and cationic 60,61 lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of the forces competing under saline conditions is no trivial exercise. As verified experimentally, salts can quickly equilibrate between external solution and the interlamellar space (18). However, because of competition between salt ions and lipid headgroups for interfacial water, incorporation of salt is only partial.…”
mentioning
confidence: 99%
“…In addition to separability, the exact functional form of these forces, especially for hydration and fluctuation, is still under debate. Although the exact values of interaction parameters obviously will depend on the choice of functional forms, the observed modification by salt is robust: weakening of vdW by monovalent salt is computed at Ϸ50% either using Helfrich power-law form for the fluctuation force (this work) or using an empirically determined exponential form (18). Once nonspecific vdW screening by salt is taken into account, specific ion adsorption, modeled at the level of additive molecular forces between bilayers, can be reconciled by assuming an effective weak binding of polarizable ions as described in the Hofmeister series.…”
Section: Separability Of Interbilayer Forcesmentioning
confidence: 99%
See 2 more Smart Citations